NEW METHODS OF TEACHING ENGLISH AS A SECOND LANGUAGE (ESL) (International journal of artificial intelligence, 2026)
The world is more interconnected than ever, and the need for effective communication across cultures has made English a global lingua franca. As a result, teaching English as a second language (ESL) has become increasingly important. Traditional methods of language instruction, such as grammar-translation and rote memorization, are giving way to innovative approaches that emphasize communication, engagement, and real-world application. This article explores several new methods of teaching ESL that have emerged in recent years, highlighting their effectiveness and practical applications.